The Long-Run Impact of Educational Expansion on Income Inequality in ASEAN Countries - Khusaini, Khusaini; Putro, Tetuko Rawidyo; Arifin, Samsul; Putra, Muhammad Hartana Iswandi; Amalia, Fitri; Syafawi, Lely (JAS (Journal of ASEAN Studies), 2025)
Over the past two decades, global income inequality has tended to increase, particularly in developing countries within the ASEAN region. Global, regional, and national efforts to narrow income inequality have been ongoing, as have research endeavours. The correlation between educational expansion and income inequality remains debatable. This research aimed to re-investigate the impact of educational expansion on income inequality across ASEAN countries. The researcher utilized panel data from 11 ASEAN member states for the period 2010 to 2021. Using Panel Fully Modified Least Square (FMOLS) analysis, the research finds that educational expansion, proxied by average years of schooling, significantly contributes to reducing income inequality in the long run. Additionally, the gross enrollment rates in secondary and higher education were found to have a strong effect on narrowing income inequality among the populations of ASEAN countries in the long term, in contrast to the impact of gross enrollment rates in primary education. These findings further reinforce the theory and previous research that education is a key factor in reducing income inequality. Therefore, governments in each country should focus on accelerating the expansion and development of secondary and higher education.